Biodistribution, shedding, and transmissibility of the oncolytic virus talimogene laherparepvec in patients with melanoma - Andtbacka, Robert H.I. (EBioMedicine, 2019)
BACKGROUND: Talimogene laherparepvec (T-VEC) is an intralesionally delivered, modified herpes simplex virus type-1 oncolytic immunotherapy. The biodistribution, shedding, and potential transmission of T-VEC was systematically evaluated during and after completion of therapy in adults with advanced melanoma. METHODS: In this phase 2, single-arm, open-label study, T-VEC was administered into injectable lesions initially at 10(6) plaque-forming units (PFU)/mL, 10(8) PFU/mL 21 days later, and 10(8) PFU/mL every 14 (±3) days thereafter. Injected lesions were covered with occlusive dressings for ≥1 week. Blood, urine, and swabs from exterior of occlusive dressings, surface of injected lesions, oral mucosa, anogenital area, and suspected herpetic lesions were collected throughout the study. Detectable T-VEC DNA was determined for each sample type; infectivity was determined for all swabs with detectable T-VEC DNA. FINDINGS: Sixty patients received ≥1 dose of T-VEC. During cycles 1–4, T-VEC DNA was detected in blood (98·3% of patients, 36·7% of samples), urine (31·7% of patients, 3·0% of samples) and swabs from injected lesions (100% of patients, 57·6% of samples), exterior of dressings (80% of patients,19·5% of samples), oral mucosa (8·3% of patients, 2·5% of samples), and anogenital area (8·0% of patients, 1·1% of samples). During the safety follow-up period, T-VEC DNA was only detected on swabs from injected lesions (14% of patients, 5.8% of samples). T-VEC DNA was detected in 4/37 swabs (3/19 patients) of suspected herpetic lesions. Among all samples, only those from the surface of injected lesions tested positive for infectivity (8/740 [1·1%]). Three close contacts reported signs and symptoms of suspected herpetic origin; however, no lesions had detectable T-VEC DNA. INTERPRETATION: Using current guidelines, T-VEC can be administered safely to patients with advanced melanoma and is unlikely to be transmitted to close contacts with appropriate use of occlusive dressings. FUND: This study was funded by Amgen Inc.: ClinicalTrials.gov, NCT02014441.